2011
DOI: 10.1515/jpm.2011.040
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal breech delivery in very low birth weight (VLBW) neonates: experience of a single center

Abstract: Neonatal outcome is not improved in VLBW infants born by cesarean section. Given the morbidity of classical cesarean sections, vaginal delivery of the breech VLBW infant may be safely considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…In their analysis, Werner et al [38] concluded that for low-birth weight neonates and preterms at 28-32WG, the delivery method did not modify the neonatal condition, but that for terms of less than 26WG, vaginal delivery accounted for only 1% of the cohort studied although it was strongly preferred. A retrospective study conducted between 1994 and 2003 in 2466 vertexpresenting singleton new-borns weighing less than 1500g compared vaginal and caesarean births [39]. In the specific subpopulation of neonates of gestational age <26 WG (n=439), caesarean showed no advantage in terms of neonatal mortality (OR 0.89; 95% CI: 0.54-1.46) [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their analysis, Werner et al [38] concluded that for low-birth weight neonates and preterms at 28-32WG, the delivery method did not modify the neonatal condition, but that for terms of less than 26WG, vaginal delivery accounted for only 1% of the cohort studied although it was strongly preferred. A retrospective study conducted between 1994 and 2003 in 2466 vertexpresenting singleton new-borns weighing less than 1500g compared vaginal and caesarean births [39]. In the specific subpopulation of neonates of gestational age <26 WG (n=439), caesarean showed no advantage in terms of neonatal mortality (OR 0.89; 95% CI: 0.54-1.46) [39].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted between 1994 and 2003 in 2466 vertexpresenting singleton new-borns weighing less than 1500g compared vaginal and caesarean births [39]. In the specific subpopulation of neonates of gestational age <26 WG (n=439), caesarean showed no advantage in terms of neonatal mortality (OR 0.89; 95% CI: 0.54-1.46) [39]. With regard to morbidity in the overall cohort, caesarean was reported not to confer any benefit for either infectious risk (OR 0.78; 95%CI: 0.61-1.01) or risk of respiratory distress (RR 1.23 [0.99-1.51]), although there was a benefit relating to the risk of cerebral haemorrhage (OR 0.73; 95% CI: 0.55-0.97) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Stohl et al (44) reported that maternal morbidities (hemorrhage and postpartum infection) were more common in mothers with fetal breech presentation and who gave birth via cesarean section.…”
Section: General Morbidity -Maternal Complicationsmentioning
confidence: 99%
“…Of the caesarean deliveries, 27 involved classical uterine incisions with higher estimated blood loss (732 mL vs 362 mL on average) and postpartum infection rates (26% vs 4%). 11 Thus, caesarean section was apparently associated with higher maternal morbidity and no neonatal benefits.…”
Section: 臀位早產胎兒最佳的分娩方法:是否達至共識?mentioning
confidence: 99%